Incidence and severity of COVID-19 infection among health care workers following vaccination: a cross sectional survey in Maharashtra - Kataria, Aditya; Priyanka Kataria; Pradeep Suryawanshi (International Journal Of Community Medicine And Public Health, 2023)
Background: Despite the vaccines against COVID-19 being proven to be effective, there is the possibility of infection despite vaccination. Such risk may be potentially greater in healthcare workers (HCWs), because of enhanced rates of exposure to the virus at the workplace. The present study was executed to estimate the incidence of COVID-19 infection post vaccination as well as to assess its severity. Methods: A cross-sectional study was initiated in field practice area of one of the tertiary health care institutes in Pune district of Maharashtra. All 700 HCWs were investigated through questionnaire method and detailed data was collected about their vaccination status and related details. Data analysed using Jeffreys’s amazing statistics program (JASP), version 0.17.1.0. Results: In the study, 29.23% of the participants showed COVID-19 infection after vaccination. The majority of clinical illnesses were of mild type. Vaccinated participants with pre-existing illnesses had more incidence of COVID-19 infection following vaccination and also the participants with complete doses had a significantly lesser rate of COVID-19 infection post vaccination compared to those with partial doses of the concerned vaccine. Conclusions: Vaccinated individuals pose less risk of severe COVID-19 infections following vaccination than those who are unvaccinated against COVID-19. Pre-existing disease is one of the major risk factors for enhanced incidence and severity of breakthrough infections.